2006
DOI: 10.1016/j.cub.2006.04.045
|View full text |Cite
|
Sign up to set email alerts
|

A Role for SUMO in Meiotic Chromosome Synapsis

Abstract: During meiotic prophase, homologous chromosomes engage in a complex series of interactions that ensure their proper segregation at meiosis I. A central player in these interactions is the synaptonemal complex (SC), a proteinaceous structure elaborated along the lengths of paired homologs. In mutants that fail to make SC, crossing over is decreased, and chromosomes frequently fail to recombine; consequently, many meiotic products are inviable because of aneuploidy. Here, we have investigated the role of the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(135 citation statements)
references
References 22 publications
6
128
0
Order By: Relevance
“…The staining of whole chromosomes with anti-SUMO antibodies indeed suggests a broad role for SUMO in these complexes (28), perhaps as a "zipping glue." However, the low steady-state level of modified Red1 and our finding that Red1 SUMOylation triggers SC formation timing (rather than SC formation itself) argue for a regulatory role instead.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The staining of whole chromosomes with anti-SUMO antibodies indeed suggests a broad role for SUMO in these complexes (28), perhaps as a "zipping glue." However, the low steady-state level of modified Red1 and our finding that Red1 SUMOylation triggers SC formation timing (rather than SC formation itself) argue for a regulatory role instead.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, Red1 SUMOylation is stimulated by the putative meiotic ligase Zip3, which is known to associate with the MRX complex and concentrates at the first meiotic DSBs (42). Zip3 also binds the central element SC protein Zip1 (42), and these proteins, together with SUMO, first localize to recombination sites before Zip1 and SUMO spread along the entire chromosome (28). Thus, Zip3 may SUMOylate only Red1 molecules that are close to the DSBs, thereby perhaps stimulating the first specific Red1-Zip1 interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synapsis initiation complex, which includes the Zip3 protein, promotes SC assembly by triggering the polymerization of Zip1 along chromosomes (18). Zip3 has SUMO E3 ligase activity and may sumoylate substrates along the chromosome cores to which Zip1 binds (19,20). In zip3 mutants, Zip1 shows severely delayed and incomplete association with meiotic chromosomes.…”
Section: Zip3 a Component Of The Synapsis Initiation Complex Regulamentioning
confidence: 99%
“…Immunofluorescence, coimmunoprecipitation and two-hybrid experiments have shown that Zip3 is an upstream player in this process which seems to be recruited at the crossover sites by its interaction with recombination proteins, and which then likely recruits other SIC/ZMM proteins (some of the SIC/ZMM proteins also exhibit interdependence for localization) including Zip2 and Zip1, promoting the latter's polymerization from the crossover sites [26,32,33,35]. Biochemically, Zip3 is a putative E3 SUMO ligase which presumably sumoylates chromosomal proteins including the LE protein Red1 [12][13][14]42]. Zip3-mediated covalent or noncovalent addition of SUMO to Red1 is proposed to trigger installation of the CE by promoting protein-protein interactions, for example, between Red1 and Zip1 [13,14].…”
Section: How Zip1 Is Recruited To Centromere?mentioning
confidence: 99%